Perceptions of the school nurse's role - Bonotan, Gilda E.
This study investigates the perceptions of administrators, classroom teachers, clinic teachers, school physicians/dentists, school nurses and pupil in Region X regarding the school nurse's role. Through random sampling, a total of 256 school personnel were given questionnaires and 360 pupils were interviewed for the survey. Chi-square analyses revealed the following findings: 1. Administrators, classroom teachers and clinic teachers have low perception of the school nurse's role; school physicians/dentists and school nurses themselves have high perception of the school nurse's role. 2. There is a significant relationship between the perception of the school nurse's role and the following variables: a. Educational attainment of classroom teachers and school nurses; b. Frequency of school nurse visits as observed by classroom teachers and clinic teachers; c. Special training in health education of school nurses; d. Special training in population and nutrition education and non-health-related training of clinic teachers; e. Grade level and sex of pupils; In addition, pupils identified the 3 most commonly-observed functions of the nurses as: (1) performing individual health inspection; (2) conducting health teachings after examinations; and, (3) performing vision test.